The Impact of Gender and Age on Attitudes toward Technology in Investment Decision-Making - Prajapati, Hetal; Ramrakhya, Divesh; Baghadiya, Jenik; Chauhan, Rahul; Maseleno, Andino; Rizal Isnanto, R (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
This research examines the influence of demographic factors—specifically gender and age - on perceptions of technology in the investment process. Using ANOVA analysis, significant differences were identified in how various demographic groups engage with investment technology, with younger respondents displaying higher familiarity and usage rates. Gender differences also revealed varying attitudes toward technology’s impact on investment decisions. The findings underscore the necessity for tailored financial products and educational resources that cater to diverse investor profiles. This study provides a foundation for future research exploring additional demographic variables, the effects of global events on investment behaviors, and the intersection of technology with socially responsible investing. Ultimately, the insights gained aim to promote inclusivity and enhance financial literacy among diverse investor populations.